Implementasi Metode Cooperative Learning Pada Mata Kuliah Microteaching Mahasiswa Universitas Sunan Giri Surabaya - masduki; El-Yunusi, Muhammad Yusron Maulana (CV. Satria Jaya, 2024)
Many learning methods are things that make it easy for teachers to apply to students and can choose what learning methods are in accordance with the needs of students. The purpose of this study was to determine the ability of postgraduate students of Sunan Giri University Surabaya in teaching Islamic Religious Education materials. This research uses a qualitative approach. Data collection techniques were conducted through interviews, observations and documentation studies. Researchers conducted a process of collecting, reducing, and concluding data, then testing the validity of the data through triangulation techniques. The results showed that the implementation of cooperative learning methods in microteaching activities was carried out using eight steps of cooperative learning. The obstacles that occur include student instability in the classroom, many students are not happy when told to work together with other students, students are worried that the work will not be divided fairly. The ways taken in overcoming these obstacles are by providing directions and reminding the learning objectives to be achieved.